The Influence of Tumor Microenvironment on ATG4D Gene Expression in Colorectal Cancer Patients - Gil, Justyna (Med Oncol, 2018)
Despite great progress in research on the subject, the involvement of autophagy in colorectal cancer (CRC) pathogenesis (initiation, progression, metastasis) remains obscure and controversial. Autophagy is a catabolic process, fundamental to cell viability and connected with degradation/recycling of proteins and organelles. In this study, we aimed at investigating the relative expression level of mRNA via Real-Time PCR of 16 chosen genes belonging to Atg8 mammalian orthologs and their conjugation system, comprising GABARAP, GABARAPL1, GABARAPL2, MAP1LC3A, MAP1LC3B, MAP1LC3C, ATG3, ATG7, ATG10, ATG4A, ATG4B, ATG4C, ATG4D, and three genes encoding proteins building the multimeric ATG16L1 complex, namely ATG5, ATG12, and ATG16L1, in 73 colorectal tumors and paired adjacent normal colon mucosa. Our study demonstrated the relative downregulation of all examined genes in CRC tissues in comparison to adjacent noncancerous mucosa, with the highest rate of expression in both tumor and non-tumor tissues observed for GAPARBPL2 and the lowest for MAP1LC3C. Moreover, in patients with advanced-stage tumors and high values of regional lymph nodes, statistically significant downregulation of ATG4D expression in adjacent normal cells was observed. Our study confirms the role of autophagy genes as cancer suppressors in colorectal carcinogenesis. Furthermore, in regard to the ATG4D gene, we observed the influence of tumor microenvironments on gene expression in adjacent colon mucosa.